More important than seeing is feeling: The influence of multimodal cospecific signals on the activities of fiddler crab leptuca uruguayensis - Martins, Carolina Guardino [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The fiddler crabs are considered key organisms of estuarine environments due to their bioturbation activities in the sediment and contribution on trophic webs. males have a hypertrophied cheliped that is commonly used to attract females through waving and also in combat with other males. the fiddler crabs have been used as a model organism in several experimental studies, mainly those related to sexual election and ecosystem engineering. in their natural environment, social interaction with other fiddler rabs (conspecific or heterospecific) is recurrent, but many studies involving this animal as model have been carried out with isolated individuals. however, the isolation of an animal can be an interfering factor in behaviors used as experimental variables. many animals can present activities dependent of the social facilitation, i.e. behavior that are stimulated by the presence of other individuals. Thus, the aim of this study was to assess whether social facilitation is a relevant factor for carrying out behaviors related to sexual selection and bioturbation in fiddler crabs Leptuca uruguayensis. In the field, we tested whether i) sexual diversity increases the activity of males fiddler crabs. we used as response variables: The number of scoops that the animal performs while feeding, the number of cheliped waves and the time out of the burrow. We found that social facilitation is a mechanism that increased the performance of waves in males of L. uruguayensis, but it was not exclusively dependent on visual stimuli. Physical interaction with other conspecific individuals may condition the crab to perform a specific behavior more frequently. Thus, it is important that future approaches with this animal model consider the effect of social facilitation as an interfering variable in its behavior.

Os caranguejos-chama-maré são considerados organismos chave dos ambientes estuarinos devido à sua atividades de bioturbação no sedimento e contribuição nas teias tróficas. Os machos têm um quelípodo hipertrofiado que é comumente usado para atrair as fêmeas através da ondulação e também em combate com outros machos. Os caranguejos-chama-maré têm sido usados como organismo modelo em diversas estudos experimentais, principalmente os relacionados à seleção sexual e engenharia de ecossistemas. Em seu ambiente natural, interação social com outros caranguejos-chama-maré (coespecíficos ou heteroespecífico) é recorrente, mas muitos estudos envolvendo este animal como modelo têm sido realizado com indivíduos isolados. No entanto, o isolamento de um animal pode ser uma fator interferente nos comportamentos utilizados como variáveis experimentais. Muitos animais podem apresentar atividades dependentes da facilitação social, ou seja, comportamentos que são estimulados pela presença de outros indivíduos. Assim, o objetivo deste estudo foi avaliar se a facilitação social é uma fator relevante para a realização de comportamentos relacionados à seleção sexual e bioturbação em caranguejos violinistas. Testamos duas hipóteses em campo: 1) A densidade da assembleia aumenta atividade dos caranguejos machos; 2) A diversidade sexual aumenta a atividade dos caranguejos machos.Usamos como variáveis de resposta: o número de colheradas que o animal realiza durante a alimentação, o número de ondas quelípedes e o tempo fora da toca. descobrimos que a sociedade. A facilitação é um mecanismo que aumentou o desempenho das ondas em machos de L. uruguayensis, mas não foi exclusivamente dependente de estímulos visuais. Interação física com outros indivíduos da mesma espécie pode condicionar o caranguejo a realizar um comportamento específico mais frequentemente. Assim, é importante que futuras abordagens com este modelo animal considerem o efeito da facilitação social como variável interferente em seu comportamento.
Mais importante do que ver é sentir: a influência de sinais coespecíficos multimodais nas atividades do caranguejo violinista leptuca uruguayensis
Keywords: Social facilitation; Leptuca uruguayensis; Experimental design; Sexual selection; Bioturbation; Crustáceos; Caranguejo; Bioturbação